The Role of ChatGPT in EFL Writing: Students’ Perspective - Capah, Catherine Rohmoia; Abrar, Mukhlash; Prapassel, Luxvhyona Fharadhylla; Sukarno, Berliana Sukma Tri (Journal of English Language and Education, 2025)
English language instruction is one of the many facets of contemporary life that ChatGPT has affected. The purpose of this study was to investigate ChatGPT's function as a writing aid for EFL students enrolled in writing classes. In particular, it looks at how the students use ChatGPT, an artificial intelligence tool. The study was carried out at one of Jambi's public universities' English departments. This study used a case study methodology in conjunction with a qualitative approach. Five English education students enrolled in writing classes participated in this study. Based on the criteria, the researcher chose the right individuals using purposive sampling. The researcher interviewed the individuals in order to collect data. The researcher applied thematic analysis to the data analysis. According to the study's findings, ChatGPT plays six roles in the writing process. They are gathering ideas, recommending references, identifying the best words and vocabulary, locating an outline or story plot, organizing the writing outcome, and even having discussions on the writing content.